Response Speed and Variability on a Verbal Stroop Task: A Small-Sample Comparison of Bilingual and Monolingual Adults. - Siren, Kathleen A.; Fossett, Tepanta R. D.; Launay-Fallasse, Sophia (Perspectives of the ASHA Special Interest Groups, 2026)
Purpose: Bilingual speakers manage two linguistic systems and often must suppress the influence of one language when using another. Practice selectively inhibiting competing linguistic information may lead to a cognitive advantage for bilingual speakers. The purpose of this study was to compare speed and accuracy of verbal responses for bilingual compared to monolingual speakers during a Stroop task, which assesses automatic processing and processing interference by presenting conflicting visual and semantic information. Method: Eight monolingual and eight simultaneous bilingual speakers completed a Stroop task in which color names were displayed in incongruent ink colors. Participants were instructed to respond verbally by identifying the ink color instead of reading the written color word. Verbal responses were assessed for both accuracy and speed of response. Results: Results showed that bilingual speakers responded more quickly and with less variability in response time compared to monolingual speakers. However, no differences in response accuracy were observed between the two groups. Conclusions: These findings align with previous research on cognitive control in bilingual compared to monolingual speakers, supporting the idea that bilingual speakers possess a cognitive advantage, particularly in tasks that demand selective attention and the inhibition of competing information. Additional research is needed to better understand the underlying mechanisms and the scope of this bilingual advantage.